The Moral Scale In Poetry Selections Al-Ihata Book: The Moral Scale In Poetry Selections Al-Ihata Book (Journal of the College of Education for Women, 2019)
Abstract:Ibn al-Khatib valuable Mokhtarath poetry as a moral standard that writercommitted to the conscious function of art, and believing that the placeliterature is determined standards of literary and alone is a (complete criticismfrom a moral stance) was adopted by the evidence of a professional imageanalogy and metaphor, and metaphor and the antagonism of the expressionof all ideas put forward is consistent with the internal rhythm arts Bdieipconsistent with the method Bhawwarith and clarity of language structure andcarried Petrakebha multiple form of expressionism. Ghani, who contrastabstraction and its proximity to the Forum staff readily near the sensory data,and the religious impact of the tendon leading sources of wisdom as well asculture compendium own experience and common humanity, and the bulk ofexoticism in the area of this formulation and content of hair .